Evaluation of the Antioxidant and Antiglycation Effects of Lactarius deterrimus and Castanea sativa Extracts on Hepatorenal Injury in Streptozotocin-Induced Diabetic Rats - Jovanović, Jelena Arambašić; Mihailović, Mirjana; Uskoković, Aleksandra S.; Grdović, Nevena; Dinić, Svetlana; Poznanović, Goran; Mujić, Ibrahim; Vidaković, Melita (Frontiers in Pharmacology, 2017)
The present study aimed to investigate the beneficial effects of the treatment with extracts from the edible mushroom Lactarius deterrimus (Ld) and the chestnut Castanea sativa (Cs), separately and in combination (MIX Ld/Cs), on oxidative stress and advanced glycation end-product (AGE)-mediated hepatorenal injury in a rat model of streptozotocin (STZ)-induced diabetes by examining pathways responsible for maintenance of redox homeostasis. An experimental model of diabetes was induced in rats by the administration of 40 mg/kg STZ intraperitoneally (i.p.) for five consecutive days. The examined extracts were applied separately at a dose of 60 mg/kg i.p. and in combination (60 mg/kg each extract; i.p.) for four weeks, starting from the last day of STZ administration. The improvement of hepatorenal function in diabetic rats treated with the extracts was associated with an improved glycemic and lipid status and suppression of oxidative stress and thereby oxidative damage of lipids and DNA. Besides the fact that both extracts inhibited protein glycation and AGE formation in vitro, they also reduced non-enzymatic glycosylation in diabetic rats in vivo. The observed antiglycation activity of the examined extracts (separately and in combination) was accompanied with the inhibition of CML-mediated RAGE/NF-κB activation and reduction of enzymatic O-GlcNAcylation in liver and kidney tissues of diabetic rats. Taken together, these results reveal that the administration of chestnut and mushroom extracts, either individually or together, activates a coordinated cytoprotective response against diabetes-induced hepatorenal injury not only through recovery of the antioxidant defense system of the cell, but also through a marked antiglycation activity.